Voltage-Dependent Emission Varying from Blue to Orange–Red from a Nondoped Organic Light-Emitting Diode with a Single Emitter - Mingxue Yang; Tian-Xiang Zhao; Si-Chao Ji; Xiao-Dong Tao; Xu-Lin Chen; Lingyi Meng; Dong Liang; Can-Zhong Lu (Nanomaterials, 2022)
Organic light-emitting diodes (OLEDs) with tunable emission colors, especially white OLEDs, have rarely been observed with a single emitter in a single emissive layer. In this paper, we report a new compound featuring a D–A–D structure, 9,9′-(pyrimidine-2,5-diylbis(2,1-phenylene))bis(3,6-di-tert-butyl-9H-carbazole) (PDPC). A nondoped OLED using this compound as a single emitter exhibits unique voltage-dependent dual emission. The emission colors range from blue to orange–red with an increase in voltage, during which white electroluminescence with a Commission Internationale De L’Eclairage (CIE) coordinate of (0.35, 0.29) and a color render index (CRI) value of 93 was observed. A comparative study revealed that the dual emission simultaneously originates from the monomers and excimers of the emitter. This study provides insight into understanding the multimer-excited mechanism and developing novel color-tunable OLEDs.